Analisis Bank Specific Factor terhadap Penyaluran Kredit Perbankan Konvensional - Aulya Sukma; Marlina Marlina; Agus Kusmana (Penerbit Goodwood, 2021)
Purpose: This research aimed to discover the influence between capital, credit risk, liquidity, and efficiency towards credit lending. Research methodology: This research includes quantitative research. The objects in this research were commercial banks listed on the Indonesia Stock Exchange (IDX), with 36 commercial banks chosen as the samples within the 2017 – 2019 period. Research hypotheses were tested with a significance level of 5% by using a panel data regression model and assisted by E-Views 11 program. Results: The result obtained within this research are (1) there is an influence between capital and credit lending, (2) credit risk does not influence credit lending, (3) liquidity has influence credit lending, and (4) efficiency does not have any influence with credit lending. Limitations: The limitations of this research were the least amount of former research both nationally and internationally containing a detailed explanation about a similar topic. Contribution: The result obtained can be used for the next researcher's references, also used as a bank’s consideration on operating their main operational activity, which is credit lending, and for investor's consideration while intended to invest in the banking sector.